Acute kidney injury: exploring endoplasmic reticulum stress-mediated cell death - Cong Cheng; Yuan Yuan; Fang Yuan; Fang Yuan; Xin Li; Xin Li (Frontiers Media S.A., 2024)
Acute kidney injury (AKI) is a global health problem, given its substantial morbidity and mortality rates. A better understanding of the mechanisms and factors contributing to AKI has the potential to guide interventions aimed at mitigating the risk of AKI and its subsequent unfavorable outcomes. Endoplasmic reticulum stress (ERS) is an intrinsic protective mechanism against external stressors. ERS occurs when the endoplasmic reticulum (ER) cannot deal with accumulated misfolded proteins completely. Excess ERS can eventually cause pathological reactions, triggering various programmed cell death (autophagy, ferroptosis, apoptosis, pyroptosis). This article provides an overview of the latest research progress in deciphering the interaction between ERS and different programmed cell death. Additionally, the report consolidates insights into the roles of ERS in AKI and highlights the potential avenues for targeting ERS as a treatment direction toward for AKI.